Alleviative effects of pinostrobin against cadmium-induced renal toxicity in rats by reducing oxidative stress, apoptosis, inflammation, and mitochondrial dysfunction - Ijaz, Muhammad Umar; Shahzadi, Sabahat; Hamza, Ali; Azmat, Rabia; Anwar, Haseeb; Afsar, Tayyaba; Shafique, Huma; Bhat, Mashooq Ahmad; Naglah, Ahmed M.; Al-Omar, Mohamed A.; Razak, Suhail (Frontiers in Nutrition, 2023)
Introduction Cadmium (Cd) is a highly toxic heavy metal that can be found everywhere in the environment and can have harmful effects on both human and animal health. Pinostrobin (PSB) is a bioactive natural flavonoid isolated from Boesenbergia rotunda with several pharmacological properties, such as antiinflammatory, anticancer, antioxidant, and antiviral. This investigation was intended to assess the therapeutic potential of PSB against Cd-induced kidney damage in rats. Methods In total, 48 Sprague Dawley rats were divided into four groups: a control, a Cd (5 mg/kg), a Cd + PSB group (5 mg/kg Cd and 10 mg/kg PSB), and a PSB group (10 mg/kg) that received supplementation for 30 days. Results Exposure to Cd led to a decrease in the activities of catalase (CAT), glutathione reductase (GSR), superoxide dismutase (SOD), and glutathione peroxidase (GSH-PX), whereas levels of reactive oxygen species (ROS) and malondialdehyde (MDA) increased. Cd exposure also caused a substantial increase in urea, kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), and creatinine levels. Moreover, a noticeable decline was noticed in creatinine clearance. Moreover, Cd exposure considerably increased the levels of inflammatory indices, including interleukin-1b (IL-1b), tumor necrosis factor-a (TNF-a), interleukin-6 (IL-6), nuclear factor kappa-B (NF-kB), inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) activity. Cd treatment decreased the expression of the antiapoptotic markers (Bcl-2) while increasing the expression of apoptotic markers (Bax and Caspase-3). Furthermore, Cd treatment substantially reduced the TCA cycle enzyme activity, such as alpha-ketoglutarate dehydrogenase, succinate dehydrogenase, malate dehydrogenase, and isocitrate dehydrogenase. Moreover, mitochondrial electron transport chain enzymes, succinatedehydrogenase, NADH dehydrogenase, cytochrome c-oxidase, and coenzyme Q-cytochrome reductase activities were also decreased following Cd exposure. PSB administration substantially reduced the mitochondrial membrane potential while inducing significant histological damage. However, PSB treatment significantly reduced Cd-mediated renal damage in rats. Conclusion Thus, the present investigation discovered that PSB has ameliorative potential against Cd-induced renal dysfunction in rats.